A Neuroligin Isoform Translated by circNlgn Contributes to Cardiac Remodeling. Issue 5 (15th July 2021) - Du, William W.; Xu, Jindong; Yang, Weining; Wu, Nan; Li, Feiya; Zhou, Le; Wang, Sheng; Li, Xiangmin; He, Alina T.; Du, Kevin Y.; Zeng, Kaixuan; Ma, Jian; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Fibrotic cardiac remodeling is a maladaptive response to acute or chronic injury that leads to arrhythmia and progressive heart failure. The underlying mechanisms remain unclear. We performed high-throughput RNA sequencing to analyze circular RNA profile in human cardiac disease and developed transgenic mice to explore the roles of circNlgn. Methods and Results: Using RNA sequencing, we found that circular neuroligin RNA (circNlgn) was highly upregulated in myocardial tissues of patients with selected congenital heart defects with cardiac overload. Back-splicing of the neuroligin gene led to the translation of a circular RNA–derived peptide (Nlgn173) with a 9-amino-acid nuclear localization motif. Binding of this motif to the structural protein LaminB1 facilitated the nuclear localization of Nlgn173. CHIP analysis demonstrated subsequent binding of Nlgn173 to both ING4 (inhibitor of growth protein 4) and C8orf44-SGK3 (serum and glucocorticoid-inducible kinase-3) promoters, resulting in aberrant collagen deposition, cardiac fibroblast proliferation, and reduced cardiomyocyte viability. Three-dimensional ultrasound imaging of circNlgn-transgenic mice showed impaired left ventricular function, with further impairment when subjected to left ventricular pressure overload compared with WT (wild type) mice. Nuclear translocation of Nlgn173, dysregulated expression of ING4 and C8orf44-SGK3, and immunohistochemical markers of cardiac fibrosis were detected in a panel of 145 patient specimens. Phenotypic changes observed in left ventricular pressure overload and transgenic mice were abrogated with silencing of circNlgn or its targets ING4 and SGK3. Conclusions: We show that a circular RNA can be translated into a novel protein isoform. Dysregulation of this process contributes to fibrosis and heart failure in cardiac overload–induced remodeling. This mechanism may hold therapeutic implications for cardiac disease.